Realisme dalam Pemikiran Ekologis - Hussin, Mutia Hariati (Jurnal Hubungan Internasional, 2012)
Environmental issues have recently become objects of study among international scholars. At the most theoretical level, a number of scholars criticize the ability of the state-system to respond to environmental dangers but at the same time the state-centric thinking still dominating most environmental activities marked by the international environmental regime formation. The two main school of thought involved in this line of enquiry are realist perspective (or paradigm) and the ecological thinking. This article analyses these two conceptions. It aims to show that although the ecological thought present themselves as radical departure from state-centric thinking, they actually reaffirm the dominant realist perspective about the centrality of the institution of the state especially when thinking about forms of formulation able to address global environmental problems.